Learning from failure: a case study of adopting radio frequency identification technology in library services. (6th April 2007) - So, Stuart C.K.; Liu, John J.
One of the biggest myths about technology is the idea that any company can easily embrace it and comfortably expect results. However, successful implementation of a technology for an organisation depends on many factors and organisation readiness is most important. The readiness of strategy, people, process and system maturity should be assured for implementing the technology successfully. Radio Frequency Identification (RFID), an automatic identification technology that aims at enhancing customer experience and improving operation efficiency, is now widely used in many business sectors. It is not uncommon that problems, such as privacy issues in handling customer information and changes in workflow, appear in various RFID applications. This article attempts to give a brief introduction to this technology, highlight possible issues in its implementation and develop strategies to tackle the problems. A case study is presented, analysing the organisation's readiness for adopting RFID technology in a medium-sized library. Future improvement is proposed through learning from implementation failure.